Administrative Burden and Business Satisfaction with Public Services - Yuan Sun; Jianing Mi; Luning Liu (Transylvanian Review of Administrative Sciences, 2025)
This study explores the relationship between businesses’ perceived administrative burdens and their satisfaction with public services, addressing a notable gap in existing literature that primarily emphasizes individual perspectives. A mixed-method approach was utilized. Initial qualitative interviews identified perceived administrative burdens in businesses using a comprehensive framework that includes learning costs, compliance costs, and psychological costs. This was followed by a quantitative analysis to evaluate the impact of these burdens on business satisfaction with public services and to validate the interrelationships among the different types of costs. The results demonstrate that all three types of administrative costs negatively impact business satisfaction. Significantly, compliance costs serve as a mediating factor, influencing satisfaction both directly and indirectly through learning and psychological costs. This study provides practical insights for improving public service delivery by mitigating administrative burdens on businesses. These enhancements can foster a more favorable environment for business-state interactions and elevate overall satisfaction with public services.